Maya Ruins, Cultural Tourism and the Contested Symbolism of Collective Identities - W. Ehrentraut, Adolf (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1996)
The more accessible archaeological sites of the ancient Maya have become cultural attractions for international mass tourism. Their development is a function of occupational and economic factors that construct an unrepresentative image of Maya civilization as a modem cultural production. While this image is part of the official heritage of modern nation states, the interaction of mass tourism and cultural resource management is creating a supranational structural framework conducive to the development of Maya ethnonationalism.